THE EFFECT OF PROFITABILITY AND GOOD CORPORATE GOVERNANCE ON EARNINGS QUALITY - Rani Aprilian; Kiagus Andi; Yunia Amelia (Jurnal Akuntansi dan Keuangan (JAK), 2020)
This study aims to examine the effect of profitability and good corporate governance on earnings quality in food and beverage companies listed on Indonesia Stock Exchange (IDX) 2015-2018 period. Profitability is calculated using Return on Assets (ROA). The proxy of Good Corporate Governance are institutional ownership, managerial ownership, audit committee, and independent commissioner. The dependent variable in this study is earnings quality measured by discretionary accrual using Modified Jones Model to detect earning management. This study used secondary data from the official website of Indonesian Stock Exchange (www.idx.co.id) and the sampling method in this study uses purposive sampling method. The data analysis in this study using multiple linear regression analysis. The results of this study indicate that profitability and audit committee have a positive effect on earnings quality, while the independent commissioner has a negative effect on earnings quality. Other independent variables i.e. institutional ownership and managerial ownership have no significant effect on earnings quality